Characterization of early immune responses elicited by live and inactivated vaccines against Johne's disease in goats - Hanafy, Mostafa; Hansen, Chungyi; Phanse, Yashdeep; Wu, Chia-wei; Nelson, Kathryn; Aschenbroich, Sophie A.; Talaat, Adel M. (Frontiers in Veterinary Science, 2023)
Mycobacterium avium subspecies paratuberculosis (M. paratuberculosis) is the causative agent of Johne’s disease, a chronic debilitating condition affecting ruminants causing significant economic losses to the dairy industry. Available inactivated vaccines are not effective in controlling the disease and vaccinated animals can continue to infect newly born calves. Recently, we have shown that a live-attenuated vaccine candidate (pgsN) is protective in goats and calves following challenge with virulent strains of M. paratuberculosis. To decipher the dynamics of the immune responses elicited by both live-attenuated and inactivated vaccines, we analyzed key immunological parameters of goats immunized through different routes when a marker-less pgsN vaccine was used. Within a few weeks, the inactivated vaccine triggered the formation of granulomas both at the site of inoculation and in regional lymph nodes, that increased in size over time and persisted until the end of the experiment. In contrast, granulomas induced by the pgsN vaccine were small and subsided during the study. Interestingly, in this vaccine group, histology demonstrated an initial abundance of intra-histiocytic mycobacterial bacilli at the site of inoculation, with recruitment of very minimal T lymphocytes to poorly organized granulomas. Over time, granulomas became more organized, with recruitment of greater numbers of T and B lymphocytes, which coincided with a lack of mycobacteria. For the inactivated vaccine group, mycobacterial bacilli were identified extracellularly within the center of caseating granulomas, with relatively equal proportions of B- and T-lymphocytes maintained across both early and late times. Despite the differences in granuloma-specific lymphocyte recruitment, markers for cell-mediated immunity (e.g., IFN-γ release) were robust in both injected pgsN and inactivated vaccine groups. In contrast, the intranasal live-attenuated vaccine did not elicit any reaction at site of inoculation, nor cell-mediated immune responses. Finally, 80% of animals in the inactivated vaccine group significantly reacted to purified protein derivatives from M. bovis, while reactivity was detected in only 20% of animals receiving pgsN vaccine, suggesting a higher level of cross reactivity for bovine tuberculosis when inactivated vaccine is used. Overall, these results depict the cellular recruitment strategies driving immune responses elicited by both live-attenuated and inactivated vaccines that target Johne’s disease